Promoting Antimicrobial Stewardship in Small Ruminants by Assessing Farmer’s Behavior and Establishing Footbath Strategy at a Community Farm in Purbalingga, Central Java - Nurzijah, Ika; Prasuma, Galar Sigit; Darmansah, Muhammad Aris; Berliana, Widya Pratiwi; Akbar, Mohammad Rekhan (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Infectious diseases such as lameness remain a persistent health problem for small ruminants in community farming systems. Although antimicrobials are frequently used as a treatment strategy, this practice contributes to increased medication use and raises concerns over antimicrobial resistance. This study assessed behavioral practices surrounding antimicrobial use among farmers at Ngudi Dadi, a community farm in Central Java, Indonesia, and implemented a multifaceted intervention combining farmer training and the construction of a biosecurity-focused footbath.Behavioral data were collected through structured survey with 21 farmers, covering five domains: antimicrobial administration, disposal of veterinary medicines, frequency of antimicrobial use, medication storage, and treatment of sick animals. Behavioral scores varied across categories, with consistently higher scores for treatment practices, but notable gaps in antimicrobial administration and disposal behaviors. Importantly, no significant correlation was observed between years of farming experience and behavioral practice scores (Spearman’s ρ = 0.0488, p = 0.8335), suggesting that practice gaps are widespread regardless of farming experience.Post-survey, a training session was conducted, followed by the construction of a footbath using lemongrass essential oil as a natural disinfectant. The footbath is now routinely used for incoming livestock at Ngudi Dadi Farm, serving as a biosecurity measure that supports reduced reliance on antimicrobials.This study represents the first initiative in Indonesia to integrate behavioral assessment, farmer education, and footbath implementation into a comprehensive antimicrobial stewardship strategy. Expansion of this model to other community farming settings, along with the development of standardized operating procedures, may enhance its scalability and long-term impact.